Microbial-based biological treatments improved the nutritional, nutraceutical and functional properties of greenhouse sweet pepper (Capsicum annuum L.) - Tahmasebi, Aminallah; Mirzaalian Dastjerdi, Abdolmajid; Jamali, Babak (Frontiers in Sustainable Food Systems, 2023)
Sweet pepper (Capsicum annum) is an important vegetable with high economic and nutritional value. The present study was conducted to evaluate the effectiveness of biological treatments on the nutritional status of greenhouse sweet peppers cv. Nirvin. Plants were divided into two categories: Peppers that were biologically treated and those that were chemically treated. The results showed that the total phenolic content, antioxidant activity, and leaf chlorophyll content were significantly higher in the biologically treated plants compared to those that received the chemical treatment. The concentration of Fe, K, Mg, P, Zn, Ca, Cu, Si and Mn also increased in biologically treated sweet pepper fruits. Fe, Mg and P content of the leaves was higher in the chemically treated plants. There was no significant difference between biological and chemical treatments in plant height as well as the number of flowers and fruits per plant. In conclusion, biological treatment could significantly improve the nutritional value of sweet peppers. Considering the risk of environmental pollution, the high cost of chemical fertilizers and pesticides, as well as their adverse impact on human health and the ecosystem, biological treatment can be a suitable alternative for sweet pepper management programs.